Spatial patterns of and risk factors for seropositivity for dengue infection - Birgit H.B. Van Benthem (2018)
Spatial patterns of and risk factors for seropositivity of dengue infection were studied in three sites in northern Thailand. A survey was conducted in 2001 among 1,750 persons. Potential risk factors for dengue infection were measured by questionnaire and IgM antibodies against dengue were detected by an enzyme-linked immunosorbent assay. The role of landscape as a risk factor was studied using land cover maps and a geographic information system. Logistic regression identified risk factors for dengue seropositivity. Spatial patterns of seropositive cases were determined by cluster analyses. Six percent of the study population was seropositive. Risk factors for dengue seropositivity differed per site, demonstrating variation in local infection patterns. In the periurban site, seropositivity depended on human behavior and factors related to housing quality rather than environmental factors. In both rural sites, older persons had a higher risk of seropositivity and persons living in houses surrounded by natural and agricultural land covers had a lower risk of seropositivity. Copyright © 2005 by The American Society of Tropical Medicine and Hygiene.